Does AI Make Medical Appointments More Convenient? An Academic Perspective on Digital Health Transformation - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming the patient experience, particularly in the realm of access and conveni...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Machine Learning